Production: what is ‘production’? - Ramesh, Sangaralingam (Henry Stewart Talks, 2019)
The production function, Factors of production, The consumer & the firm, Physical product (average, marginal, total), Returns (increasing, diminishing, zero, negative), The law of diminishing returns, Returns to scale, Scale of production, Long-run & short-run average cost curves